2010
DOI: 10.1016/s0140-6736(10)60934-8
|View full text |Cite|
|
Sign up to set email alerts
|

Efficacy of boceprevir, an NS3 protease inhibitor, in combination with peginterferon alfa-2b and ribavirin in treatment-naive patients with genotype 1 hepatitis C infection (SPRINT-1): an open-label, randomised, multicentre phase 2 trial

Abstract: SummaryBackground Peginterferon plus ribavirin achieves sustained virological response (SVR) in fewer than half of patients with genotype 1 chronic hepatitis C virus infection treated for 48 weeks. We tested the effi cacy of boceprevir, an NS3 hepatitis C virus oral protease inhibitor, when added to peginterferon alfa-2b and ribavirin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
464
1
21

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 622 publications
(494 citation statements)
references
References 26 publications
8
464
1
21
Order By: Relevance
“…In contrast, a Phase 2 study of boceprevir previously suggested that lowering HCV RNA levels with a 4-week peginterferon/ribavirin pretreatment may reduce the emergence of protease-resistant variants, decrease viral breakthrough rates during treatment, and increase SVR rates. 24 Regarding previous peginterferon/ribavirin response, on-treatment virologic failure and the emergence of resistant variants were more frequent in prior null responders than in prior partial responders and prior relapsers. This is not surprising given that, by definition, prior null responders failed to achieve a !2 log 10 reduction in HCV RNA by week 12 of previous peginterferon/ribavirin treatment, and therefore two components of the telaprevir triple therapy regimen would not have been fully functional in these patients.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In contrast, a Phase 2 study of boceprevir previously suggested that lowering HCV RNA levels with a 4-week peginterferon/ribavirin pretreatment may reduce the emergence of protease-resistant variants, decrease viral breakthrough rates during treatment, and increase SVR rates. 24 Regarding previous peginterferon/ribavirin response, on-treatment virologic failure and the emergence of resistant variants were more frequent in prior null responders than in prior partial responders and prior relapsers. This is not surprising given that, by definition, prior null responders failed to achieve a !2 log 10 reduction in HCV RNA by week 12 of previous peginterferon/ribavirin treatment, and therefore two components of the telaprevir triple therapy regimen would not have been fully functional in these patients.…”
Section: Discussionmentioning
confidence: 98%
“…HCV RNA ''<25 IU/mL, target not detected'' is also described as undetectable HCV RNA in the study. HCV RNA levels were measured at the following study visits: screening, baseline, day 3, weeks 1, 2, 4, 5,6,8,10,12,14,16,20,24, and 36, end of treatment (week 48 or time of early discontinuation), and at follow-up visits 4, 12, and 24 weeks after the end of treatment. HCV RNA levels were also assessed at week 72 for all patients, including those who discontinued early.…”
Section: Methodsmentioning
confidence: 99%
“…En effet, les nouvelles drogues ont une activité pangénotypique, il n'y a pas de résistance génotypique croisée entre les différentes classes d'antiviraux directs, et d'autres types de traitement sont en cours de développement. Ces autres antiviraux, tels que les inhibiteurs de la cyclophiline, les inhibiteurs d'entrée du virus dans les cellules, les ARN anti-sens, ainsi que la vaccinothérapie, permettront, dans les situations les plus difficiles, de dépasser un génotype 1), avec une réduction de 48 à 24 semaines de la durée du traitement chez la moitié des patients (ceux qui ont une réponse virologique rapide définie par l'absence de détection du virus après 4 semaines de traitement) [15][16][17][18][19][20]. La limite principale de ces traitements est celle des effets secondaires, en plus de ceux liés au traitement classique : effets cutanés (télaprévir) avec des rashs sévères dans 5 à 10 % des cas [21], et une anémie (télaprévir ou bocéprévir) [22].…”
Section: Revuesunclassified
“…boceprevir Phase 1 and phase 2 trials established the efficacy and optimal dosing of boceprevir in combination with pegIFN and ribavirin for both treatment-naive and treatment-experienced patients (13,14). Interestingly, the use of a four-week lead-in phase with SOC before initiating boceprevir achieved greater response rates in treatmentnaive patients in the Serine Protease Inhibitor Therapy 1 (SPRINT-1) trial (14). The lead-in phase theoretically decreases rates of resistance by initiating the protease inhibitor at lower viral loads.…”
Section: Efficacymentioning
confidence: 99%